Isolation of Carrageenan from Eucheuma cottonii by Variying Alkaline Solutions - Gaspersz, Nelson; Tanasale, Matheis F. J. D. P.; Malle, Dominggus; Kafara, Zulvia Astrianti (Indonesian Journal of Chemical Research, 2025)
The carrageenan can be isolated by combining alkaline KOH, NaOH, and Ca(OH)2 solutions. Alkaline solutions of KOH: NaOH, KOH: Ca(OH)2, and NaOH: Ca(OH)2 were combined to extract carrageenan. The amount of the solution was varied, the carrageenan groups were characterized using FTIR, and the carrageenan’s gel strength was tested. The extraction results obtained the highest yield in the combination of alkaline solutions Ca(OH)2 80%+KOH 20%, which is equal to 70.18% FTIR test results for carrageenan produced from the extraction of Eucheuma cottonii seaweed showed absorption showing the type of kappa (κ) carrageenan. The highest gel strength test results were obtained in an alkaline solution of Ca(OH)2 80%: NaOH 20%, which was 252.5 g bloom, and the lowest was made in a solution of Ca(OH)2 80%: KOH 20%, which was 21.0 g bloom.